2014
DOI: 10.1002/ece3.1146
|View full text |Cite
|
Sign up to set email alerts
|

Diet alters delayed selfing, inbreeding depression, and reproductive senescence in a freshwater snail

Abstract: Reproductive success is a critical fitness attribute that is directly influenced by resource availability. Here, we investigate the effects of diet-based resource availability on three interrelated aspects of reproductive success: a change in mating system based on mate availability, consequent inbreeding depression, and the deterioration of reproductive efficiency with age (senescence). We employed a factorial experimental design using 22 full-sib families of the hermaphroditic freshwater snail Physa acuta to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Theory predicts an optimal waiting time before commencing self-fertilization, related to the intensity of inbreeding depression in the progeny, the ability to re-allocate reproductive resources to later fecundity and the probability of finding a partner versus dying as the individual ages (Tsitrone et al, 2003a). Empirical evidence for delayed selfing in line with these predictions comes from a variety of hermaphroditic organisms, including plants (Kalisz et al, 1999;Qu et al, 2007), freshwater snails (Tsitrone et al, 2003b;Auld & Henkel, 2014; but see Escobar et al, 2007), cestodes (Schjørring, 2004, but see Schärer & Wedekind, 1999 and the flatworm M. hystrix, which delays reproduction for up to 50% of the average age at first outcrossing, when forced to self (Ramm et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…Theory predicts an optimal waiting time before commencing self-fertilization, related to the intensity of inbreeding depression in the progeny, the ability to re-allocate reproductive resources to later fecundity and the probability of finding a partner versus dying as the individual ages (Tsitrone et al, 2003a). Empirical evidence for delayed selfing in line with these predictions comes from a variety of hermaphroditic organisms, including plants (Kalisz et al, 1999;Qu et al, 2007), freshwater snails (Tsitrone et al, 2003b;Auld & Henkel, 2014; but see Escobar et al, 2007), cestodes (Schjørring, 2004, but see Schärer & Wedekind, 1999 and the flatworm M. hystrix, which delays reproduction for up to 50% of the average age at first outcrossing, when forced to self (Ramm et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…Mean ages at first reproduction, last reproduction, and death (±1 SE ) for Physa acuta reared under two different diets (Lettuce or Spirulina) and two different mate treatments (mated or isolated). Age at first reproduction was reported and discussed in Auld and Henkel () and is redrawn here for comparison. The difference between the age at last reproduction (ALR) and the age at first reproduction (AFR) is the reproductive life span (RL), the difference between age at death at ALR is the post‐reproductive life span (PRL)…”
Section: Resultsmentioning
confidence: 99%
“…When individuals have more access to mating partners they initiate reproduction early and their life span in shortened, but the relative duration of reproductive life span is unknown. When individuals are not given access to mating partners, they delay the onset of reproduction (i.e., delayed self‐fertilization; Auld, , Auld & Henkel, ), and we can expect a consequent delay in the onset of reproductive senescence. Previous work evaluating the effects of mating system on relative rate of reproductive senescence has shown that reproductive function of mated snails tends to senesce faster than in unmated snails (Auld & Henkel, ), but this comparison is only based on the first few reproductive events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Auld et al. ), and that reproductive senescence is affected by diet (Auld and Henkel ). While considerably less is known about the physiological effects of predation risk in mollusks, snails do exhibit stress hormone responses involving corticotropin (Ottaviani et al.…”
mentioning
confidence: 99%